Bat adaptations in inflammation and cell death regulation contribute to viral tolerance - Subham Das; Disha Jain; Priyansh Chaudhary; Rita M. Quintela-Tizon; Arinjay Banerjee; Sannula Kesavardhana (mBio)
ABSTRACT Bats are reservoirs for multiple viruses, some of which are known to cause global disease outbreaks. Virus spillovers from bats have been implicated in zoonotic transmission. Some bat species can tolerate viral infections, such as infections with coronaviruses and paramyxoviruses, better than humans and with less clinical consequences. Bat species are speculated to have evolved alongside these viral pathogens, and adaptations within the bat immune system are considered to be associated with viral tolerance. Inflammation and cell death in response to zoonotic virus infections prime human immunopathology. Unlike humans, bats have evolved adaptations to mitigate virus infection-induced inflammation. Inflammatory cell death pathways such as necroptosis and pyroptosis are associated with immunopathology during virus infections, but their regulation in bats remains understudied. This review focuses on the regulation of inflammation and cell death pathways in bats. We also provide a perspective on the possible contribution of cell death-regulating proteins, such as caspases and gasdermins, in modulating tissue damage and inflammation in bats. Understanding the role of these adaptations in bat immune responses can provide valuable insights for managing future disease outbreaks, addressing human disease severity, and improving pandemic preparedness.